Factorize: y^3 - 1  

3 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

To factorize `y^3 - 1` use the relation `a^3 - b^3 = (a - b)*(a^2 + ab + b^2)`

Substitute a^3 with y^3 and b^3 with 1 = 1^3. This gives:

y^3 - 1

= y^3 - 1^3

= (y - 1)(y^2 + y + 1)

The factorized form of y^3 - 1 is (y - 1)(y^2 + y + 1)

pramodpandey's profile pic

pramodpandey | College Teacher | (Level 3) Valedictorian

Posted on

we know a^3-b^3=(a-b)(a^2+b^2+ab)

here a=y and b=1 ,so we  have

y^3-1=(y-1)(y^2+1+y)

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

`y^3 - 1`

`(y-1)(y^2+y+1)`

We’ve answered 318,924 questions. We can answer yours, too.

Ask a question